ANALISIS YURIDIS PENANGGULANGAN TINDAK PIDANA PEREDARAN MINUMAN KERAS - Al Wafi, Wildan Hazmi; Widodo, Ernu; Damayanti, Sri Sukmana; Aribawa, Muhammad Yustino (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Indonesia is a country governed by the rule of law, as stipulated in Article 1 paragraph (3) of the 1945 Constitution, which is based on law and justice for its citizens. One issue that is of great concern and requires serious attention from the government is the widespread consumption of alcoholic beverages by the general public. The misuse of alcoholic beverages, such as consuming them beyond reasonable limits, can harm oneself and, more broadly, pose problems for society. Essentially, the misuse of alcoholic beverages violates several legal regulations as stipulated in the Civil Code (KUHP), with violations related to alcohol misuse outlined in Articles 536, 537, 538, and 539. The purpose of this study is to determine the role of the police in combating the circulation of alcoholic beverages, as well as the obstacles and solutions faced by the police in combating the circulation of alcoholic beverages. The research method used in this study is the normative legal approach, which involves conducting legal research by examining literature or secondary data. The role of the police in the implementation of prevention and combating the misuse of alcoholic beverages. The role of the police in implementing the prevention of the sale and abuse of alcoholic beverages in the community by the Kediri City Police is realised in three types of preventive actions, namely: pre-emptive efforts, preventive efforts, and repressive efforts. Pre-emptive efforts involve community outreach and education. Preventive efforts include surveillance in high-risk areas, raids, patrols, and inspections. Repressive efforts involve arresting offenders and disrupting the distribution channels of alcoholic beverages. The challenges faced include community efforts to protect alcohol sellers, leaks of raid information, and overly lenient legal penalties. Solutions to these challenges include adopting a persuasive approach with the community, holding limited joint meetings, and increasing resources.